MARKET RISKS: SUPERVISION AND REGULATION - G. T. Saparova (Финансы: теория и практика)
All the world’s financial markets and their segments are subject to risks. Fighting risk is not effective and useless, as they will still occur at varying intervals, and their appearance on one segment may affect the other or all at once. Therefore, the question is considered in terms of minimization and hedging, but it is impossible to exclude regulatory measures from the government.Currency legislation of the Republic of Kazakhstan is based on the Constitution of the Republic of Kazakhstan, the Law of the Republic of Kazakhstan “About Currency Regulation and Currency Control” and other normative legal acts of the Republic of Kazakhstan.The situation in the deposit market is an indicator not only of the banking sector, but also the economy as a whole. Fluctuations in commodity exports and adjustment of the national currency could have a serious negative impact on the stability of the whole economic system of the state.Recent events in Russia showed without government support, many banks are not able to show their worth, at a mass outflow of deposits from them. Further actions to improve the key rate and increase the guaranteed sum insured will gradually lead to normalization and return of confidence among the population.All these measures have been carried out in Kazakhstan in 2009 after a sharp devaluation (as opposed to the Russian Federation), but early enough and such a stir arose.At present, all of the risks of devaluation risk is the highest, therefore, the population tends to move their savings and savings in real assets. Nevertheless, the outflow of funds from banks is not observed and the mortgage remains one of the real instruments in the financial market. Risks that are shaking the world economy can not get around Kazakhstan, and thus the introduction of international requirements is difficult.Thus, based on our review identified some positive and negative aspects of the implementation of Basel III in Kazakhstan can be attributed to the negative, then that part of the requirements established by the regulator at this point can not be implemented by banks and there is no direct impact on the risk profile of the bank; the same applies to the pluses, what organized system of risk management and internal control and management of liquidity risk.